A study to assess the effectiveness of a health education programme on awareness regarding breast self-examination among females - Rashmi Singh (International Journal Of Community Medicine And Public Health, 2026)
Background: Breast cancer remains a major public health concern among women, and limited awareness regarding breast self-examination may delay early recognition and timely reporting of breast-related abnormalities. Methods: This pre-experimental one-group pre-test post-test study was conducted during November 2025 among females selected according to the study criteria. A structured knowledge questionnaire was used to assess awareness regarding breast self-examination before and after the health education programme. The pre-test was conducted first, followed by the planned health education programme. After the intervention, a post-test was conducted using the same questionnaire. The collected data were analyzed using descriptive and inferential statistics. Results: The post-test awareness score was higher than the pre-test awareness score, showing improvement in awareness regarding breast self-examination after the health education programme. The findings showed that the health education programme was effective in improving awareness among females. Conclusions: The health education programme was effective in improving awareness regarding breast self-examination among females.